PENERAPAN PENDEKATAN RME DENGAN MEDIA KONKRET UNTUK MENINGKATKAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN RUANG PADA SISWA KELAS V SDN JATIMALANG TAHUN AJARAN 2015/2016 - Wulandari, Rina (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract. The Use of Realistic Mathematics Education (RME) Approach Using Concrete Objects in Improving Mathematics Learning about Three-Dimensional Shape for the Fifth Grade Students of SD Negeri Jatimalang in the Academic Year of 2015/2016. The objectives of this research is to improve Mathematics learning about three-dimensional shape in the application of using RME approach using concrete objects. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research showed that the application of using RME approach using concrete objects can improve Mathematics learning about three-dimensional shape for the fifth grade students of SD Negeri Jatimalang in the academic year of 2015/2016.Keywords: RME, concrete objects, three-dimensional shapeAbstrak. Penerapan Pendekatan Realistic Mathematics Education (RME) dengan Media Konkret untuk Meningkatkan Pembelajaran Matematika tentang Bangun Ruang pada Siswa Kelas V SD N Jatimalang Tahun Ajaran 2015/2016. Tujuan penelitian ini untuk meningkatkan pembelajaran matematika tentang bangun ruang dengan menerapkan pendekatan RME dengan media konkret. Penelitian Tindakan Kelas dilaksanakan dalam tiga siklus terdiri dari perencanaan, pelaksanaan, observasi, refleksi. Hasil penelitian menunjukkan penerapan pendekatan RME dengan media konkret dapat meningkatkan pembelajaran matematika tentang bangun ruang. Persentase ketuntasan siswa pada siklus I = 89,29%, siklus II = 91,08% dan siklus III = 96,28%. Simpulan penelitian ini adalah penerapan pendekatan RME dengan media konkret dapat meningkatkan pembelajaran matematika tentang bangun ruang pada siswa kelas V SD N Jatimalang tahun ajaran 2015/2016.Kata kunci: RME, Media Konkret, Bangun Ruang